Consumers’ ability to distinguish between milk types: results of blind taste testing - Glanz, Karen (Fam Community Health, 2020)
OBJECTIVE: To assess consumers’ ability to correctly identify different types of milk in a blind taste test and correlates of plans to purchase lower-fat milk. METHODS: Adults from eight supermarkets in low-income neighborhoods tasted three types of unlabeled lower-fat or fat-free milk samples and guessed the type of each sample. RESULTS: Of the 1074 participants, only 7.6% were able to identify all three unlabeled samples correctly. CONCLUSIONS AND IMPLICATIONS: Most adults in this study reported consuming higher-fat milk and could not correctly identify milk type by taste alone. Blind taste tests may encourage consumers to drink lower-fat milk.